2022
DOI: 10.3390/plants11152048
|View full text |Cite
|
Sign up to set email alerts
|

Irrigation Regimes and Nitrogen Rates as the Contributing Factors in Quinoa Yield to Increase Water and Nitrogen Efficiencies

Abstract: Sustainable field crop management has been considered to reach the food security issue due to global warming and water scarcity. The effect of deficit irrigation and nitrogen rates on quinoa yield is a challenging issue in those areas. In this regard, the interaction effects of different N rates (0, 125, 250, and 375 kg N ha−1) and irrigation regimes [full irrigation (FI) and deficit irrigation at 0.75 FI and 0.5 FI] on quinoa yield and water and nitrogen efficiencies were evaluated with a two-year field exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Bharami et al [ 4 ] studied the yield response of quinoa cv. Titicaca under field conditions in Iran and showed that the application of 75% of full irrigation requirements led to NO 3 -N accumulation in upper soil layers, thus facilitating nitrogen uptake and reduced nitrate loss to deeper layers of the soil and allowing for a reduction in the optimal nitrogen fertilization level for the study area.…”
Section: Ecophysiological Traits and Adaptabilitymentioning
confidence: 99%
“…Bharami et al [ 4 ] studied the yield response of quinoa cv. Titicaca under field conditions in Iran and showed that the application of 75% of full irrigation requirements led to NO 3 -N accumulation in upper soil layers, thus facilitating nitrogen uptake and reduced nitrate loss to deeper layers of the soil and allowing for a reduction in the optimal nitrogen fertilization level for the study area.…”
Section: Ecophysiological Traits and Adaptabilitymentioning
confidence: 99%
“…Specifically, under-and over-fertilization reportedly have a significant effect on crop yield, with a reduced DM partitioning ratio of vegetative organs, and a reduced material basis for yield formation under conditions of low fertility [33,34]. In contrast, excessively high fertilization causes vegetative organs to grow, resulting in a decrease in the proportion of DM partitioning to the seeds [35]. Conversely, rational K application promotes photosynthate transport to reproductive organs [36].…”
Section: Potassium Fertilization Promoted Dry Matter Accumulationmentioning
confidence: 99%
“…Quinoa responded positively to nitrogen fertilization (Bahrami et al 2022). Thus, using organic fertilizers constitutes a sustainable solution to improve soil fertility for a long period of time which has positive effect on the succeeding crops (Bhalshakar 2020).…”
Section: Introductionmentioning
confidence: 99%